Exceptio Dilatoria in the Indonesian Context: Implementation of Justice and Legal Certainty from Radbruch's Perspective - Ashari, Zahrah Salsabillah; Jamilah (Pustaka Peradaban, 2024)
Exceptio dilatoria is an exception that states that a lawsuit filed with the Religious Court cannot be granted because it is premature. Until now, exceptio dilatoria is a problem that still often arises in the civil world. As for the consequences of the application of exceptio dilatoria, it is not uncommon for it to be a burdensome decision for one of the aggrieved parties. This study aims to analyze the legal considerations made by the panel of judges in deciding a lawsuit that is considered premature. By attaching several decisions from the lawsuit divorce case that was decided as a premature lawsuit. This study also analyzes the legal consequences of the existence of exceptio dilatoria in the case of contested divorce on the theory of legal justice and the theory of legal certainty. The research method used is normative juridical with case approach method. The results show that exceptio dilatoria is a problem that cannot be avoided as long as there is no legal rule governing it. This can be seen from the inconsistency of judges in applying exceptio dilatoria in cases of contested divorce. So that the considerations made by the panel of judges in applying exceptio dilatoria still cannot meet the standards of justice and legal certainty as formulated by Gustav Radburch. Exceptio dilatoria adalah suatu eksepsi yang menyatakan bahwa gugatan yang diajukan ke Pengadilan Agama tidak dapat dikabulkan karena prematur. Hingga saat ini, exceptio dilatoria merupakan masalah yang masih sering muncul dalam dunia perdata. Konsekuensi dari penerapan exceptio dilatoria tidak jarang menjadi keputusan yang memberatkan salah satu pihak yang dirugikan. Penelitian ini bertujuan untuk menganalisis pertimbangan hukum yang dilakukan oleh majelis hakim dalam memutus gugatan yang dianggap prematur. Dengan melampirkan beberapa putusan dari kasus gugatan cerai yang diputus sebagai gugatan prematur. Penelitian ini juga menganalisis akibat hukum dari keberadaan exceptio dilatoria dalam kasus perceraian yang disengketakan berdasarkan teori keadilan hukum dan teori kepastian hukum. Metode penelitian yang digunakan adalah yuridis normatif dengan metode pendekatan kasus. Hasil penelitian menunjukkan bahwa exceptio dilatoria adalah masalah yang tidak dapat dihindari selama belum ada aturan hukum yang mengaturnya. Hal ini dapat dilihat dari inkonsistensi hakim dalam menerapkan exceptio dilatoria dalam kasus perceraian yang disengketakan. Sehingga pertimbangan yang dilakukan oleh majelis hakim dalam menerapkan exceptio dilatoria masih belum dapat memenuhi standar keadilan dan kepastian hukum sebagaimana yang diformulasikan oleh Gustav Radbruch.